Focal Segmental Glomerulosclerosis Patient Baseline Characteristics in the Sparsentan Phase 3 DUPLEX Study - Howard Trachtman; Jai Radhakrishnan; Michelle N. Rheault; Charles E. Alpers; Jonathan Barratt; Hiddo J.L. Heerspink; Irene L. Noronha; Vlado Perkovic; Brad Rovin; Hernán Trimarchi; Muh Geot Wong; Alex Mercer; et al. (Kidney International Reports)
Introduction: The phase 3 DUPLEX trial is evaluating sparsentan, a novel, nonimmunosuppressive, single-molecule dual endothelin angiotensin receptor antagonist, in patients with focal segmental glomerulosclerosis (FSGS). Methods: DUPLEX (NCT03493685) is a global, multicenter, randomized, double-blind, parallel-group, active-controlled study evaluating the efficacy and safety of sparsentan 800 mg once daily versus irbesartan 300 mg once daily in patients aged 8 to 75 years (USA/UK) and 18 to 75 years (ex-USA/UK) weighing ≥20 kg with biopsy-proven FSGS or documented genetic mutation in a podocyte protein associated with FSGS, and urine protein-to-creatinine ratio (UP/C) ≥1.5 g/g. Baseline characteristics blinded to treatment allocation are reported descriptively. Results: The primary analysis population includes 371 patients (336 adult, 35 pediatric [<18 years]) who were randomized and received study drug (median age, 42 years). Patients were White (73.0%), Asian (13.2%), Black/African American (6.7%), or Other race (7.0%); and from North America (38.8%), Europe (36.1%), South America (12.7%), or Asia Pacific (12.4%). Baseline median UP/C was 3.0 g/g; 42.6% in nephrotic-range (UP/C >3.5 g/g [adults]; >2.0 g/g [pediatrics]). Patients were evenly distributed across estimated glomerular filtration rate (eGFR) categories corresponding to chronic kidney disease (CKD) stages 1 to 3b. Thirty-three patients (9.4% of 352 evaluable samples) had pathogenic or likely pathogenic (P/LP) variants of genes essential to podocyte structural integrity and function, 27 (7.7%) had P/LP collagen gene (COL4A3/4/5) variants, and 14 (4.0%) had high-risk APOL1 genotypes. Conclusions: Patient enrollment in DUPLEX, the largest interventional study in FSGS to date, will enable important characterization of the treatment effect of sparsentan in a geographically broad and clinically diverse FSGS population.